Computer-Based Validation of 3n+1 Hypothesis for Numbers 3n−1 - Srdjan Kadic; Savo Tomovic (Tehnički Vjesnik, 2019)
The formulation of the 3n−1 problem is simple but no one has found the solution yet. This paper transforms the original problem into its equivalent so that it becomes more suitable for computer validation. A new algorithm is proposed and implemented. The hypothesis is tested and proven to be valid for numbers 3n−1, conclusive with number 332768−1.